Fireproof properties of wood plastic composite produced with different forest species and recycled thermoplastics - Martínez López, Yonny; Paes, Juarez Benigno; Martínez Rodríguez, Emilio (Instituto de Ecología, A.C., 2018)
Wood and thermoplastic waste can be used to produce new forest products with better properties and higher benefit. The objective of the research was to evaluate the fire retardant properties of wood plastic boards made from wood waste (sawdust) from different forest species (Pinus caribaea, Pinus cubensis, Cedrela odorata, Talipariti elatus and Eucalyptus sp.), recycled thermoplastics (polyethylene of low and high density, polyethylene terephthalate and polypropylene), chemical additives (calcium carbonate, stearic acid, calcium stearate, zinc stearate and coupling agent) and tetrabrik as flame retardant. The boards were produced on a laboratory scale and processed by extrusion. The flame retardant properties were evaluated by reaction and fire resistance tests according to the European Standard (UNE EN) 13823. The developed treatments showed good response to the reaction and resistance to fire; treatment 6 showed the best results. The extraction of the resin from pine wood allowed the boards to improve their fire retardant properties. The highest levels in terms of the effects of fire can be obtain by mixing all the raw materials in equitable proportions, which provide the boards with better properties. The proposed methodology for the production of wood plastic boards can be developed on a large scale by the board industry, given its low cost-quality-benefit. In this way, sustainable use of industrial waste and its conversion into useful materials for society can be achieved.